Forkhead Box Protein P3 in the Immune System - Yohei Sato (Allergies)
Regulatory T cells (Tregs) play a central role in immune regulation and tolerance. The transcription factor FOXP3 is a master regulator of Tregs in both humans and mice. Mutations in FOXP3 lead to the development of IPEX syndrome in humans and the scurfy phenotype in mice, both of which are characterized by fatal systemic autoimmunity. Additionally, Treg dysfunction and FOXP3 expression instability have been implicated in nongenetic autoimmune diseases, including graft-versus-host disease, inflammatory bowel disease, rheumatoid arthritis, and multiple sclerosis. Recent investigations have explored FOXP3 expression in allergic diseases, revealing Treg alterations in food allergies, asthma, and atopic dermatitis. This review examines the multifaceted roles of FOXP3 and Tregs in health and various pathological states, including autoimmune disorders, allergic diseases, and cancer. Additionally, this review focuses on the impact of recent technological advancements in facilitating Treg-mediated cell and gene therapy approaches, including CRISPR/Cas9-based gene editing. The critical function of FOXP3 in maintaining immune homeostasis and tolerance to both self-antigens and alloantigens is emphasized. Considering the potential involvement of Tregs in allergic diseases, pharmacological interventions and cell-based immunomodulatory strategies may offer promising avenues for developing novel therapeutic approaches in this field.